PERBEDAAN PERSEPSI KUALITAS, KEPUASAN, DAN LOYALITAS KONATIF PENGUNJUNG MUSEUM KOTA BANDA ACEH (STUDI PADA MUSEUM TSUNAMI ACEH DAN MUSEUM ACEH) - Novi Astuti, Jeliteng Pribadi (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This research conducted to investigate the difference in perceived quality, satisfaction, and conative loyalty on museum visitors in Banda Aceh. Data collected as many as 100 questionnaires. The sample in this research was the visitors who had visited the Museum Tsunami Aceh and Museum Aceh. The sampling technique used in this research is purposive sampling. Technique of analysis using different test average pairwise (Paired Sample T Test). Based on t-test results found that there is no difference between the perceived quality, satisfaction, and visitors conative loyalty at Museum Tsunami Aceh and Museum Aceh. Keywords: Perceived Quality, Satisfaction, Conative Loyalty